Effect of carbon and nitrogen sources on mycelial biomass and biosynthesis of antifungal protein from Aspergillus giganteus MTCC 8408 in submerged fermentation - Dutta D.; Debnath Das M. (My University, 2025)
The objective of the present study was to determine the role of macroelements (various carbon and nitrogen sources) with various physical parameter (pH, temperature, slant age and inoculum volume) on both mycelial growth and extracellular antifungal protein (afp) production optimization in submerged culture of Aspergillus giganteus MTCC 8408. Maximum production of growth associated afp was observed with soluble starch as carbon source and corn step liquor (CSL) with proteose peptone (PP) as organic nitrogen source. The optimal temperature and initial pH for both mycelial growth and afp production by Aspergillus giganteus in submerge culture were 25°C and 6.3, respectively. Soluble starch at 30 g/1 was the most suitable carbon source for maximum mycelial growth. Shifting from glucose to soluble starch (2%) supplemented with CSL (2%) and Proteos Peptone (1%) caused a shift from pelleted morphology to dispersed, ‘pulp-like’ morphology with consequent increase in afp production. Maximum specific growth rate (µ) and specific rate of product formation (Qp) were 0.012 h-1 and 0.0026, respectively. Slant age at 5 days old and inoculum level at 5% (v/v) appeared to have profound effect on afp production. Under optimal culture condition, mycelial biomass growth was enhanced by 1.22 times with growth associated afp production by 2.21 times compared to the basal Olson medium. © 2017, Scientific Publishers. All rights reserved.